PEMBENTUKAN SATGAS BERBASIS KARANG TARUNA DALAM PENANGGULANGAN BENCANA PANDEMI COVID-19 - Pulungan, Rafiah Maharani; Hardy, Fathinah Ranggauni; Nasrullah, Nanang; Wiradati, Meidy; Ainaya, Nabila Aulia; Sergio, Diego (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The establishment of the COVID-19 Task Force is one strategy that can be taken to prevent and control COVID-19 cases in the Pasir Putih District area. The goal is that the community can participate in the implementation of the prevention and control of COVID-19 in their respective areas of residence. In addition, this activity can also increase knowledge related to COVID-19 and spread the latest information about COVID-19. Thus, the number of spread and transmission of COVID-19 will soon decrease and the situation will return to normal. The target of this service activity is the youth group in Pasir Putih District, Depok City. The implementation method of this service activity includes the stages of preparation, implementation, and evaluation. The result of this activity is an increase in the knowledge of youth youth groups related to the prevention and control of COVID-19.